Biofilm production in relation to extended spectrum beta-lactamase production and antibiotic resistance among uropathogenic Escherichia coli - Khatri, Samip; Pant, Narayan Dutt; Neupane, Sanjeev; Bhandari, Suman; Banjara, Megha Raj (Janaki Medical College Journal of Medical Science, 2017)
Not available. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(1): 61-63